2002
DOI: 10.1139/t02-006
|View full text |Cite
|
Sign up to set email alerts
|

Vibratory compaction of coarse-grained soils

Abstract: The variation of the coefficient of earth pressure in normally consolidated and overconsolidated soil and the effect of soil compaction on the change of the horizontal effective stress are discussed based on cone penetration test (CPT) data. A method is outlined for estimating the increase in the effective earth pressure based on sleeve friction measurements. Soil compaction increases not only soil density, but also horizontal effective stress. Since the cone stress is influenced by the vertical and horizontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 13 publications
1
19
0
6
Order By: Relevance
“…In line with this, Matsuo (2004) stated that aged alluvial sand is systematically more resistant to liquefaction than recently deposited manmade islands, even if normalised N 1 values are identical. Although Skempton (1986) suggested the increase of SPT-N over 100 years, Mesri et al (1990), Baxter & Mitchell (2004), Mitchell & Solymer (1984) and Massarsch & Fellenius (2002) stated that the increase of SPT-N or CPT (cone penetration test) resistance is completed within 1 year after land construction or significant compaction. This short-term increase of SPT-N value implies that the ageing of SPT-N cannot account for the observed improvement in liquefaction resistance that occurs over a timescale of hundreds or thousands of years.…”
Section: Previous Studies On Ageing Of Soilmentioning
confidence: 99%
“…In line with this, Matsuo (2004) stated that aged alluvial sand is systematically more resistant to liquefaction than recently deposited manmade islands, even if normalised N 1 values are identical. Although Skempton (1986) suggested the increase of SPT-N over 100 years, Mesri et al (1990), Baxter & Mitchell (2004), Mitchell & Solymer (1984) and Massarsch & Fellenius (2002) stated that the increase of SPT-N or CPT (cone penetration test) resistance is completed within 1 year after land construction or significant compaction. This short-term increase of SPT-N value implies that the ageing of SPT-N cannot account for the observed improvement in liquefaction resistance that occurs over a timescale of hundreds or thousands of years.…”
Section: Previous Studies On Ageing Of Soilmentioning
confidence: 99%
“…Because the present paper addresses the high vulnerability of liquefaction in very recent subsoil having the age of only decades or one hundred years, the engineering ageing is the topic to be discussed. Noteworthy is that SPT blow counts and other sounding resistance increase as well with time and, more interestingly, Baxter and Mitchell (2004) as well as Mitchell and Solymer (1984) and Massarsch and Fellenius (2002) reported that the increase occurs in a time scale of weeks or months only. In line with this, Fig.…”
Section: On Soil Ageingmentioning
confidence: 99%
“…In vibrocompaction, the vibrator is used in granular soils, and the vibration compacts the surrounding soil. The soil densification is the most important effect of vibrocompaction, and has been mainly analysed using field measurements [6,7], as it is difficult to model the process numerically [8]. In contrast, stone columns are typically used in soft cohesive soils, as these cannot be compacted.…”
Section: Introductionmentioning
confidence: 99%